Targeting the PD-1/PD-L1 Axis in Human Vitiligo - Willemsen, Marcella; Melief, Cornelis J. M.; Bekkenk, Marcel W.; Luiten, Rosalie M. (Frontiers in Immunology, 2020)
Autoreactive CD8+ T cells play a pivotal role in melanocyte destruction in autoimmune vitiligo. Immunotherapy for melanoma often leads to autoimmune side-effects, among which vitiligo-like depigmentation, indicating that targeting immune checkpoints can break peripheral tolerance against self-antigens in the skin. Therapeutically enhancing immune checkpoint expression on immune cells or skin cells making self-reactive T cells anergic, seems a promising therapeutic option for vitiligo. Here we review the current knowledge on the PD-1/PD-L1 pathway in vitiligo as new therapeutic target for vitiligo therapy.